Culture, Identity, and Indigenous Knowledge Systems in Contemporary Society: Tradition as a Living Social Practice - Gjylbegaj, Valjeta; Hafizi, Alma (European Journal of Social Science Education and Research, 2025)
This article examines early twentieth-century European travelogues as living archives of cultural heritage with implications for intercultural education and indigenous knowledge systems. Focusing on Northern Albania, the study reconceptualizes travel literature by Erich Liebert, Karl Steinmetz, William Le Queux, and Paul Siebertz as ethnographic sources documenting practices of social order, identity formation, and cultural continuity. Through qualitative interpretive methodology anchored in cultural anthropology and critical heritage studies, the analysis demonstrates how foreign observers documented hospitality, dwelling practices, landscape relations, and moral codes as living heritage transmitted through embodied experience. The research contributes to heritage studies by theorizing these narratives as intercultural mediation, providing pedagogical resources for intercultural education and interpretive cultural tourism.  In contemporary society, where cultural identities are negotiated between globalizing forces and local resistance, the indigenous knowledge systems documented offer alternative models for social cohesion, intercultural ethics, and sustainable community practices. These narratives offer a model for social pedagogy promoting empathy and intercultural cooperation.
Keywords: living heritage, cultural resilience, intercultural education, indigenous knowledge systems, social pedagogy, globalization, identity formation, heritage preservation